QUIZIZZ APPLICATION FOR ENGLISH ONLINE LEARNING: THE STUDENTS’ PERCEPTIONS - Eka Wulandari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Education and technology are becoming indispensable nowadays. The pandemic outbreak also hastens all things up. This also applies to the English teaching and learning process that should be done by using a hybrid learning system, which combines direct interaction and an online platform. Due to that condition, a suitable online-based learning media should be applied to support the process. Quizizz application is one of the learning media that can be considered to be employed since it has attractive features and design. The research described in this article was aimed to find out the level of the students’ satisfaction with the use of Quizizz for learning English. It also presented survey data about students’ perceptions on the use of the Quizizz application for English online learning. The population involved 68 students of the Health Promotion Study Program, Poltekkes Kemenkes Malang. The data was collected by applying an online questionnaire form, presented in the form of percentage data, and analyzed by using a descriptive explanation. The results showed a high perception of the students on the use of Quizziz for English online learning which can be seen through the result of the survey that showed a high percentage of students’ satisfaction in regards to the application. Regarding the result of the study, it is recommended for teachers to consider utilizing this application to create meaningful and engaging online learning interactions.